Landfarming of petroleum wastes in a cold dry climate of Tierra del Fuego: Effect on soil and vegetation - Mendoza, Rodolfo Ernesto (2000)
The effect of adding organic oily wastes on plant cover and on soil water content was studied in a soil covered by a community of low forage value in Tierra del Fuego (Argentina). Oily wastes were mixed with the top 3 cm of the soil in May 1993 at rates of 1.51 and 3.03 % (w/w basis). In December 1993, half of each plot was fertilized with N and P, and changes in species abundance and total cover were evaluated in December of 1994 and 1995. Soil samples at 0-3, 3-6 and 6-9 cm depths were taken in December of 1993-1995, and analyzed for pH, water content, and total petro- leum hydrocarbon (TPH). The oily wastes increased water content and pH in the soil. Fertilization increased plant growth but both fertilization and oily waste increased plant cover. TPH in soil decreased from 3 % to 0.18 % during the experimental period, but fertilization did not affect the decrease in TPH with time. The results, combined with the annual rainfall and the water table elevation at the site, suggests that the risk of contaminating the water table is relatively low. It is concluded that landfarming could be applied as a remedial action in soils of Tierra del Fuego. In addition, amending the soil with oily waste in dry heath ecosystems increased water conservation and this effect promoted plant growth.